Analisis Implementasi Sistem Penilaian pada Kurikulum Merdeka di SDN Pondok Jengkol Kabupaten Tangerang - Magdalena, Ina; Anisa, Dela; Salsabila, Nada; A, Tarisa Amalia (TSAQOFAH, 2023)
The final assessment in the SDN environment isbthe goalkof thislstudy, whichgaims tojdetermine whether or not the implementation of learning design is successful. An implementation is one that is meticulously planned and executed. A straightforward definition of the term "implementation of learning" would be "applicationpof learningdinlgeneral." An activity in summativedassessment results in numerical or numerical scores that are used to evaluate a student's performance. If the unit of learninglexperience orfthe entiredsubject matterchas beenxcompleted, this assessment activity is carried out. By reading, recording, and processing research materials, a qualitative description method waskusedraspthedresearchnmethod. Accordingdto theifindings ofkthe study, the diagnostic assessment aims to identify students' initial conditions and basic abilities. Non-cognitive diagnostic assessment and cognitive diagnostic assessment are the two types of diagnostic assessment. The goal of the Merdeka Learningxcurriculum is toxfoster ahpositive learningaenvironment. Theigoalhof independentjlearningkis to create a happy environment for teachers, students, and parents.